Literature Study: Analysis of the Use of Video as a Student Learning Media - Wijaya, Abung Supama; Suriaatmaja Suwanda, Bayu; Febri Astuti, Vivien; Siskandar, Ridwan (Jurnal Sains Indonesia, 2022)
This article describes the results of a literature study on using video as a medium for student learning. This article is part of research on developing learning videos among students to support the achievement of educational goals in higher education. The literature study was carried out as a survey of research articles on using video as a student learning media published in national journals and proceedings using Indonesian. The study's results were analyzed descriptively into three main study focuses: 1) the orientation of the use of video as a student learning media, 2) the software used in producing learning videos, and 3) the types of videos used as learning media. The results of this literature study are expected to be a reference for lecturers and developers of learning videos to produce a variety of varied and quality learning videos